Characterization of beta‐lactamase and biofilm producing Enterobacteriaceae isolated from organized and backyard farm ducks. (2nd July 2019) - Banerjee, A.; Bardhan, R.; Chowdhury, M.; Joardar, S.N.; Isore, D.P.; Batabyal, K.; Dey, S.; Sar, T.K.; Bandyopadhyay, S.; Dutta, T.K.; Samanta, I.
Abstract: This study was undertaken to detect the occurrence of beta‐lactamase and biofilm producing Enterobacteriaceae in healthy ducks. A total 202 cloacal swabs were collected from ducks kept in organized ( n  = 92) and backyard ( n  = 110) farms in West Bengal (India). The ducks had no history of antibiotic intake. Among the 87 phenotypically beta‐lactamase producing Escherichia coli, 19 (17·43%), 6 (5·05%) and 15 (13·76%) isolates possessed blaTEM, blaSHV and blaCTX‐M respectively. Whereas, 5 (38·46%) Salmonella isolates were found to harbour blaCTX‐M . In K. pneumoniae 10 (33·33%), 3 (13·33%), 4 (13·33%) isolates possessed blaTEM, blaSHV and blaCTX‐M respectively. The sequences of selected PCR products were found 98% cognate with blaCTX‐M‐9, blaSHV‐12 and blaTEM‐1 . Beta‐lactamase producing E. coli isolates belonged to 14 different serogroups such as O1, O2, O3, O5, O7, O8, O35, O83, O84, O88, O119, O128, O145 and O157. Moreover, 87 E. coli (79·82%), six Samonella (46·15%) and 13 K. pneumoniae (43·33%) isolates were detected as AmpC producers possessing blaAmpC . Majority of E. coli (46·79%), Salmonella (46·15%) and K. pneumoniae (70%) isolates were detected as biofilm producers and possessed the associated genes ( csgA, sdiA, rcsA, rpoS ). Significantly higher occurrence of beta‐lactamase and biofilm producing Enterobacteriaceae isolates was detected in backyard ducks than organized farms. Significance and Impact of the Study: Consumption of antibiotic through feed or during therapy is considered as potential reason for generation of antimicrobial resistant bacteria in birds. This study provides valuable evidence that exposure to contaminated environment may be an additional source for generation of antimicrobial resistant bacteria in backyard ducks. The backyard ducks are reared by marginal farmers in India who cannot offer antibiotics to them either through feed or during therapy due to high cost. The study also reveals a significant correlation between biofilm formation and possession of antimicrobial resistance genes in the bacterial isolates from the ducks. Abstract : Significance and Impact of the Study: Consumption of antibiotic through feed or during therapy is considered as potential reason for generation of antimicrobial resistant bacteria in birds. This study provides valuable evidence that exposure to contaminated environment may be an additional source for generation of antimicrobial resistant bacteria in backyard ducks. The backyard ducks are reared by marginal farmers in India who cannot offer antibiotics to them either through feed or during therapy due to high cost. The study also reveals a significant correlation between biofilm formation and possession of antimicrobial resistance genes in the bacterial isolates from the ducks.